NMR crystallography of monovalent cations in inorganic matrixes: Li+ siting and the local structure of Li+ sites in ferrierites1. Issue 43 (28th May 2015) - Klein, P.; Dedecek, J.; Thomas, H. M.; Whittleton, S. R.; Pashkova, V.; Brus, J.; Kobera, L.; Sklenak, S.
<x xml:space="preserve">Abstract</x> A new approach to the determination of the Li+ siting and the local structure of Li+ sites in zeolites is reported.